Platelet concentrates for bone regeneration: Current evidence and future challenges. (17th February 2018) - Badran, Zahi; Abdallah, Mohamed-Nur; Torres, Jesus; Tamimi, Faleh
Abstract: Activated platelet concentrates are autologous blood preparations containing supraphysiological concentration of platelets. Platelet concentrates are commonly used for bone regeneration purposes based on the fact that growth factors released from activated platelets alpha granules have osteoinductive effects on bone cells. Although most preclinical and clinical studies show that platelet concentrates improve the outcomes of bone regeneration procedures, some studies reported conflicting results and even negative effects on bone healing. Several confounding parameters have been suggested as possible reasons for such inconsistencies (i.e. preparation and activation methods). However, heterogeneity in clinical studies makes drawing evidence-based conclusions difficult. On the other hand, recent findings show that the constituents of platelets dense granules (i.e. serotonin, ATP, Ca 2+ ) have potential inhibitory effects on bone metabolism. Accordingly, we suggest that a partial explanation for the conflicting results could be the potential negative effects that dense granules may have on bone healing.